FEMINISASI KEMISKINAN: ANTARA TAFSIR AGAMA DAN REALITAS SOSIAL. (STUDI KASUS DI KECAMATAN SOKO KABUPATEN TUBAN) - Almas'udah Almas'udah (LPPM Institut Agama Islam Al-Hikmah Tuban, 2014)
Poverty has become a social reality that exists in every country in the world and has been for centuries. Social reality requires certain levels of society, and all layers have a size of each, can be from employment, position, breadth of knowledge, wealth, political, and religious descent. In measuring poverty, the government has put on poverty measurement approach that made the world body, such as the UNDP (United Nations Development Programme). UNDP sees poverty from two aspects, namely: poor income such as apparel, home, as well as basic necessities of food. And poor human capabilities, such as illiteracy, malnutrition, short life expectancy, education, sanitation, communication in general to support the sustainability of basic human capabilities. Poverty is the case in this country is poverty that women face, or the feminization of poverty. Feminization of poverty in Indonesia has several factors, namely: early marriage, divorce, education, social, cultural, and economic factors. These factors will be discussed along with the views of the author of the context of Islam in society. Because, however, the reality that occurs in the community is not as simple as religious texts. Would be interesting to discuss in this study, the author examines the female heads of household poverty in Sub Soko Tuban, causes of female heads of household poverty and how solutions to solve them.